Does Ethical Leadership Matter in Indonesia’s Public Sector? The Mediating Role of Ethical Climate - Dekri Firmansyah; Riani Rachmawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
Amid the emergence of various problems of ethical violations at the global and local levels in Indonesia, especially in the public sector, many parties demand various efforts to improve ethical behavior both at the official and staff levels. This study aims to analyze the influence of ethical leadership and ethical climate on employee ethical behavior, moderated by person-organization fit in the context of state financial organization (Organisasi Keuangan Negara/OKN). Using quantitative research methods with Partial Least Square Structural Equation Modeling (PLS-SEM), this research examines the relationship between these variables through a survey of 898 respondents within the Indonesian state financial organization. The findings suggest that ethical leadership has a significant positive impact on ethical climate and employee ethical behavior. Moreover, ethical climate plays a partial mediating role between ethical leadership and employee ethical behavior. However, person-organization fit could not strengthen the relationship between ethical climate and employee ethical behavior. This study contributes to the literature by providing empirical evidence on the role of leadership and organizational climate in fostering ethical behavior among public sector employees. The findings offer practical implications for policymakers in enhancing ethical governance.